2013
DOI: 10.1103/physreve.87.032306
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of micellar polycrystals under time-dependent volume fraction conditions

Abstract: We study the freezing kinetics of colloidal polycrystals made of micelles of Pluronic F108, a thermosensitive copolymer, to which a small amount of silica nanoparticles of size comparable to that of the micelles are added. We use rheology and calorimetry to measure T c , the crystallization temperature, and find that T c increases with the heating rateṪ used to crystallize the sample. To rationalize our results, we first use viscosity measurements to establish a linear mapping between temperature T and the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Remaining seeds then are either distributed throughout the sample or populate the grain boundaries of the emerging crystals. Their accumulation there is assisted by annealing processes [81,365] and a foam-like microstructure appears similar to that observed for long lasting annealing of AS crystals [298,299]. Cleaning of contaminated crystals can be achieved by processes analogous to zone melting [366].…”
Section: Heterogeneous Nucleationmentioning
confidence: 77%
“…Remaining seeds then are either distributed throughout the sample or populate the grain boundaries of the emerging crystals. Their accumulation there is assisted by annealing processes [81,365] and a foam-like microstructure appears similar to that observed for long lasting annealing of AS crystals [298,299]. Cleaning of contaminated crystals can be achieved by processes analogous to zone melting [366].…”
Section: Heterogeneous Nucleationmentioning
confidence: 77%
“…The colloidal crystals have been described elsewhere [29][30][31]. They comprise a commercial blockcopolymer, water and nanoparticles.…”
Section: Experimental Samplesmentioning
confidence: 99%
“…3B), a trend opposite to that measured without NPs. Microscopy and scattering experiments [29,30] indicate that when Ṫ increases the average size of the crystallite decreases. Hence, the total surface of grain boundaries, where we expect dissipation to occur predominantly, increases.…”
Section: Visco-elasticity Of Samples Doped With Nanoparticlesmentioning
confidence: 99%
“…Their extensive use is also motivated by the facile means that leads to their synthesis and manipulation, coupled to their direct characterization by several non-destructive techniques [25]. Among the recent studies in this field, a new strategy emerged and consisted of adding small amounts of nanoparticles (NPs) to a system of different nature [26][27][28][29][30][31][32][33][34]. It was successfully shown that when a phase transition is induced in such a system, microscopic segregation occurs and results in polycrystalline grains separated by nanoparticle (NP) rich interstices.…”
mentioning
confidence: 99%
“…Moreover, as the phase transition temperature is reached, the NPs are being segregated outside the micrograins whose equilibrium size is, in turn, controlled by the NPs. This effect was explained by studying the evolution of grain size as a function of the two tuning parameters: NP volume fraction and crystallization rate in a nearly similar colloidal system [28,29]. Accordingly, it was shown that the presence of NPs decreases the energy barrier to nucleation and favors the formation of smaller crystalline nuclei through reduction of the surface term in Gibbs energy.…”
mentioning
confidence: 99%